Processing math: 100%

Pages

Bookmark and Share

Wednesday, September 20, 2017

ODE discrete version

If f is a function that is defined over natural numbers (f:N \to R), let f^* denote the function f^*(n) = f(n) - f(n-1). Find all functions such that n(f^*)^*(n) + (n-1)f^*(n) = f(n) for all n > 2

Solution We can check that f(n) = A(n-1) + B/2^n for any constant A,B satisfies the given equation. Now we show that there's nothing else.

Define g = f^*+f. The equation is identical to: n(f^*+f)^*(n) =(f^*+f)(n) n(g(n) - g(n-1)) = ng^*(n) = g(n) \frac{g(n)}{n} = \frac{g(n-1)}{n-1} for all n>2, therefore g(n)/n must be a constant. Remember that g(1) is not defined because f is only defined for n \geq 1 thus g is only defined for n \geq 2. Furthermore, the value g(2) depends on f(1) and f(2).

Case 1: g(2) = 0 In this case then g(n) = 0 \forall n. (f^*+f)(n) = 0 f(n) = f(n-1)/2 so we easily get f(n) = k/2^n for some constant k.

Case 1: g(2) \neq 0 Note that if f is a solution to the problem then kf is also a solution to the problem, for all k real numbers. If we replace f by kf, then g is also replaced by kg. So WLOG, we may assume that g(2) = 2

Because g(n) / n is a constant then g(n) / n = g(2) / 2 = 1 so g(n) = n \forall n >2 f(n) = \frac{f(n-1) + n}{2} for all n > 2.

Because g(2) = 2 = 2f(2) - f(1) then f(2) = 1+ f(1)/2 Now notice this pattern: f(3) = \frac{f(2) + 3}{2} = 2 + f(1)/4 f(4) = \frac{f(3) + 4}{2} = 3 + f(1)/8 Easy to prove by induction that f(n) = n-1 + f(1)2^{1-n}.

From the two cases above, it's clear that any solution of the equation must be in the form of f(n) = A(n-1) + B/2^n for any constant A,B

No comments:

Post a Comment